Public health financing and infant mortality: does governance quality matter? - Sirag, Abdalla; Mohamed Nor, Norashidah; Raja Abdullah, Nik Mustapha; Abd Ghani, Judhiana (Southern Public Administration Education Foundation, 2017)
Public finance of health care is known to be one of the central factors for improving population health status. Since healthcare works through public institutions, the effect of public health financing on its outcome relies on the level of governance quality. The current paper examines the impact of public health financing on a health outcome (infant mortality) taking governance quality into consideration. The study uses panel data analysis for 171 countries categorized into three income levels: low-income, middle-income and high-income countries, for the period 1995–2012. In addition, some techniques that can help to reduce the bias associated with the potential endogeneity problem, such as GMM estimators, are adopted to obtain less biased results. The findings reveal the importance of public health financing in improving the population’s health. In particular, public health financing is negatively associated with the infant mortality rate in all income groups. Moreover, socioeconomic factors, such as income and education, appear to be equally important in reducing the infant mortality rate. Most importantly, the quality of governance was found to be relevant in determining the effect of public health financing on the population’s health. Our study provides partial evidence to show that public finance of healthcare is more efficient in improving the population’s health in countries where governance quality is relatively high compared to countries with low quality of governance.